Electronic interaction in composites of a conjugated polymer and carbon nanotubes: first-principles calculation and photophysical approaches - Massuyeau, Florian; Wéry, Jany; Duvail, Jean-Luc; Lefrant, Serge; Yaya, Abu; Ewels, Chris; Faulques, Eric (Beilstein Journal of Nanotechnology, 2015)
The mechanisms that control the photophysics of composite films made of a semiconducting conjugated polymer (poly(paraphenylene vinylene), PPV) mixed with single-walled carbon nanotubes (SWNT) up to a concentration of 64 wt % are determined by using photoexcitation techniques and density functional theory. Charge separation is confirmed experimentally by rapid quenching of PPV photoluminescence and changes in photocurrent starting at relatively low concentrations of SWNT. Calculations predict strong electronic interaction between the polymer and the SWNT network when nanotubes are semiconducting.
Keywords: composite; conjugated polymer; DFT calculations; energy transfer; photoconductivity; single wall carbon nanotubes; time-resolved photoluminescence